A New Nested Allele-Specific Multiplex Polymerase Chain Reaction Method for Haplotyping of VKORC1 Gene to Predict Warfarin Sensitivity - Yung, An Chua; Abdullah, Wan Zaidah; Yusof, Zukurnai; Siew, Hua Gan (Hindawi Publishing Corporation, 2014)
The vitamin K epoxide reductase complex 1 gene (VKORC1) is commonly assessed to predict warfarin sensitivity. In this study, a new nested allele-specific multiplex polymerase chain reaction (PCR) method that can simultaneously identify single nucleotide polymorphisms (SNPs) at VKORC1 381, 861, 5808, and 9041 for haplotype analysiswas developed and validated. ExtractedDNAwas amplified in the first PCR DNA, which was optimized by investigating the effects of varying the primer concentrations, annealing temperature, magnesium chloride concentration, enzyme concentration, and the amount of DNA template. The amplification products produced from the first round of PCR were used as templates for a second PCR amplification in which both mutant and wild-type primers were added in separate PCR tubes, followed by optimization in a similar manner. The final PCR products were resolved by agarose gel electrophoresis and further analysed by using a VKORC1 genealogic tree to infer patient haplotypes. Fifty patients were identified to have H1H1, one had H1H2, one had H1H7, 31 had either H1H7 or H1H9, one had H1H9, eight had H7H7, and one had H8H9 haplotypes. This is the first method that is able to infer VKORC1 haplotypes using only conventional PCR methods.